Study of factors contributing to female infertility - Shinde, Kiran Parsuram; Krovi, Nagasundari; Dhutraj, Pooja Gangadhar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Infertility is a global issue in reproductive health. All over the world, infertility is viewed as a social stigma, which causes social, economic and psychological consequences. Methods: A prospective, observational study was conducted at south central railway hospital, Secunderabad in 100 women aged between 18-40 years with complaints of primary and secondary infertility. We aimed to find the incidence of different causes of infertility in the females attending Gynaecology OPD over a period of 2 years. Results: Different causes of infertility were studied. In the present study ovarian factors (50%) was the most common factor for infertility followed by tubal factors (22%), uterine factors (20%) and peritoneal factors (19%) respectively. Conclusions: PCOS was found to be a contributing factor in both primary and secondary infertility, maybe because of increased sedentary lifestyle and physical inactivity and the study population being from an urban background.